Assessment of the cytotoxic mechanisms of β-sitosterol in a pancreatic cancer cell line: An in silico and in vitro study - Lopez, Kianna Denise F. (Animo Repository, 2024)
Pancreatic cancer recently observed a rise in incidence and prevalence in terms of cancer-related mortality worldwide. Although recent modifications in chemotherapy, radiation therapy, and immunotherapy provide increased options for treatment, the survival rate of pancreatic cancer compared to other types of malignancies is still relatively low. β-sitosterol has been found to show incredible potential as an anticancer compound in a variety of disease models given its ability to inhibit cell proliferation, induce apoptosis, and instigate cell cycle arrest. However, there is a limited amount of studies that investigate its activity in pancreatic cancer models. The study gives an insight on the activity of β-sitosterol in pancreatic cancer cells via assessment of the potential of soybean-derived β-sitosterol as a drug candidate through an in silico pharmacokinetic ADMET analysis and its cytotoxic capabilities. The ADMET study was able to predict that soybean-derived β-sitosterol is an ideal drug candidate based on three properties: metabolism, excretion, and toxicity. Various dosages of soybean-derived β-sitosterol (0, 5, 15, 30, 60, and 150-μM) were able to demonstrate cytototoxic outcomes after a 24-hour treatment period. The compound was found to be potent enough to induce cytotoxicity at a lower dosage based on its IC50 value of 2.685-μM. Molecular docking studies showed that AGR2 had the highest binding affinity with the ligand interacting at the A-chain of the protein through a variety of favorable non-bond interactions (i.e., hydrophobic interactions, van der Waals interactions, etc.). Through this study we hope to contribute to understanding the underlying mechanism as to how β-sitosterol interacts with pathogenic pancreatic proteins which may pave the way for the development of more effective cancer treatments.